تقييم أسئلة اللغة العربية للامتحانات المدرسية على المستوى الوطني بإندونيسيا في ضوء تصنيف بلوم المعدل للأهداف المعرفية : دراسة وصفية تحليلية - عبد المبارك، إيماك (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Assessment is one of the most important things in the process of learning and teaching. The test is one of the tools used in the assessment process worldwide. This study aims to identify and analyze the levels of the Arabic questions available in the Ujian Sekolah Berstandar Nasional (USBN) in Indonesia during the academic year 2015-2019 according to Revised Bloom's Taxonomy of cognitive aims (remembering, understanding, applying, analyzing, evaluating and creating). To achieve the purpose of this study, the researcher used the descriptive analytical method as an analysis unit to analyze the questions. The total number of questions are 470. It was taken from two educational levels (Lower and Upper-Secondary). Based on the study, the results indicate that Arabic questions for the USBN focused on the lower-order thinking skills. The findings indicate that 51% of all the questions are categorized as understanding level. Within the understanding level, it consists of five cognitive processes (inferring 38%, translating 32%, summarizing 15%, exemplifying 14%, and explaining 1%). The findings also indicate that 20% of all questions are categorized as applying level. It consists of implementing 90% and executing 10%. The remembering level which consists of recalling 56% and recognizing 44%, are 16% of all questions. On the other side, 13% of the questions are categorized in the analyzing level. It consists of two cognitive processes (organizing 65% and differentiating 35%). The other two levels; evaluating and creating, receive 0%, respectively.